Inovasi Manajemen Pendidikan Anak Usia Dini dalam Meningkatkan Mutu Lembaga Raudhatul Athfal (RA) Aisyiyah Sidoharjo - Ahmad Nur Ismail; Dea Ari Wahyu Prayesti; Dhea Alifa Noviany; Edy Suprayitno (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
Innovating in education is essential, as educational management innovation plays a crucial role in enhancing the quality of learning and the efficiency of managing early childhood education facilities, as demonstrated in early childhood education at RA Aisyiyah Sidoharjo. This case study allows us to transform the nature of innovation in education, innovation in extracurricular activities, and innovation in implementing work programs. This qualitative study featuring a case analysis necessitates data-gathering methods that include detailed observation, discussions with the RA leader and the teaching board, and documentary proof. The gathered data is subsequently examined through data reduction, data visualization, and conclusion. The study’s results indicate that the effective implementation of technology for fostering innovation in learning and enhancing branding institutions through social media tools has been achieved. The execution of a project-based curriculum has not been fully optimized, but it benefits from numerous extracurricular programs that enhance students’ skills and creativity through activities like reading and writing, drum bands, mini Reyog, dancing, and Quran recitation, all of which are carried out very effectively. Through this joint innovation, it can enhance education and health initiatives, boost the competitiveness of organizations, and elevate the quality of institutions.